1999
DOI: 10.1080/01496399908951147
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Antimonic Acid as Column-Packing Material for Chromatographic Lithium Isotope Separation

Abstract: The applicability of granular cubic antimonic acid (C-SbA) as column packing material in chromatographic lithium isotope separation was investigated. The feed solution should have the buffer capacity to promote lithium uptake, and its pH has to be kept as low as 2.25 to prevent the decomposition of the granular C-SbA in order to obtain a sharp front boundary of the lithium sorption zone. The pH and the chemical composition of the eluent should be finely controlled to obtain a displacement-type chromatogram. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…It is seen that ( 7 Li= 6 Li) i =( 7 Li= 6 Li) orig was a monotonously decreasing function of the effluent volume and asymptotically approached the original value with increasing effluent volume. Thus, the heavier isotope of lithium was enriched in the frontal part of the breakthrough chromatogram, meaning that the same isotope was preferentially fractionated in the solution phase as was usually the case with the ion exchange system (1,3,5). This trend in the lithium isotope fractionation agreed with that found in the batch experiment.…”
Section: Synthesis Of Zirconium Phosphate 3693supporting
confidence: 79%
See 1 more Smart Citation
“…It is seen that ( 7 Li= 6 Li) i =( 7 Li= 6 Li) orig was a monotonously decreasing function of the effluent volume and asymptotically approached the original value with increasing effluent volume. Thus, the heavier isotope of lithium was enriched in the frontal part of the breakthrough chromatogram, meaning that the same isotope was preferentially fractionated in the solution phase as was usually the case with the ion exchange system (1,3,5). This trend in the lithium isotope fractionation agreed with that found in the batch experiment.…”
Section: Synthesis Of Zirconium Phosphate 3693supporting
confidence: 79%
“…It has been reported that some inorganic ion exchangers show larger lithium isotope effects, from several times to over one order of magnitude, than those of organic ion exchangers. They include niobic and tantalic acids (2), antimonic acids (3)(4)(5), and titanium(IV)=zirconium(IV) phosphates (6,7). Rhombohedral zirconium(IV) phosphate, HZr 2 (PO 4 ) 3 , designated hereafter as HZP, shows cation exchange properties.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques in common use for Li isolation involve chromatography with a variety of ion exchange media. The combined need for both good elemental purifi cation and maximum Li yield has lead to the development of a plethora of techniques for Li separation chemistry in Earth materials (Chan 1987;Oi et al 1997Oi et al , 1999Moriguti and Nakamura 1998a;Tomascak et al 1999a).…”
Section: Requirements In Chemical Separationmentioning
confidence: 99%
“…It is reported that some inorganic ion exchangers, [1][2][3][4][5][6][7] including metal(IV) phosphate-based ion exchangers, show large lithium isotope effects compared to organic ion exchangers. In previous papers, we reported the selectivity of alkali metal ion and lithium isotopes on HZr 2 (PO 4 ) 3 prepared form NH 4 Zr 2 (PO 4 ) 3 5) and HTi 0.5 Zr 1.5 (PO 4 ) 3 prepared from MTi 0.5 Zr 1.5 (PO 4 ) 3 (M=Li, Na). 6) HZr 2 (PO 4 ) 3 and HTi 0.5 Zr 1.5 (PO 4 ) 3 are lithium ion-specific among alkali metal ions and isotopically 6 Li-specific.…”
Section: Introductionmentioning
confidence: 99%